Answer: B) 25
=============================================
Work Shown:
g(x) = x-7
g(3) = 3-7 .... replace every x with 3
g(3) = -4
f(g(3)) = f(-4) .... replace g(3) with -4
f(x) = x^2+9
f(-4) = (-4)^2+9
f(-4) = 16+9
f(-4) = 25
f(g(3)) = 25
-------------------------
Another approach:
f(x) = x^2 + 9
f( g(x) ) = ( g(x) )^2 + 9 ... replace every x with g(x)
f( g(x) ) = ( x-7 )^2 + 9 ... plug in g(x) = x-7
f( g(3) ) = ( 3-7 )^2 + 9 .... plug in x = 3
f( g(3) ) = ( -4 )^2 + 9
f( g(3) ) = 16 + 9
f( g(3) ) = 25